Circadian pacemaker function and entrainment during maturation of transgenic hypertensive TGR(mREN2)27 and Sprague-Dawley rats - Canal-Corretger, Maria Mercè; Witte, Klaus; Lemmer, Björn (Chronobiology international, 2001)
TGR(mREN2)27 (TGR) transgenic rats develop hypertension due to the mouse mRen-2 gene inserted in their genome. At 5 weeks of age, the blood pressure of TGR rats starts rising, until a maximum is reached at 10 weeks of age. Adult TGR rats show peak values of blood pressure (BP) during the light phase, while heart rate (HR) and motor activity (MA) peak at night. In the present experiment, we evaluated the evolution of circadian rhythms in motor activity, heart rate, and blood pressure of TGR and Sprague-Dawley (SD) rats under 12h light-dark cycles (LD 12:12). Results confirmed that the blood pressure of TGR rats starts to increase at 5 weeks of age, reaching a plateau by the 11th week. Parallel to the increase in blood pressure levels, there was a decrease in the period length of the blood pressure rhythm, a delay in the onset of the alpha phase of the blood pressure rhythm with respect to that of motor activity and heart rate, and a decrease in heart rate levels. In all of the variables studied, the alpha phase of SD rats always started before darkness, whereas that of TGR rats started after lights off. In general, heart rate and motor activity levels of TGR rats were higher than those of SD rats. The amplitude of the circadian rhythms studied was greater in TGR rats than in SD rats. The present results suggest that the different evolution of circadian rhythms in TGR and SD rats might be due to differences in the functioning of the entrainment pathway or the circadian clock itself, which can be detected in young rats and that are probably caused by the expression of the mouse transgene.